2021
DOI: 10.1021/acs.est.1c01057
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Transplacental Transfer of Per- and Polyfluoroalkyl Substances: Prenatal Exposure Levels, Characteristics, and Mechanisms

Abstract: Prenatal exposure to perfluoroalkyl and polyfluoroalkyl substances (PFASs) has aroused public concerns as it can pose multiple health threats to pregnant women and cause adverse birth outcomes for fetuses. In previous studies, the prenatal exposure levels and transplacental transfer efficiencies (TTE) of PFASs have been reported and discussed. Specifically, the binding affinities between PFASs and some transporters were determined, demonstrating that the TTE values of PFASs are highly dependent on their bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 99 publications
3
61
0
Order By: Relevance
“…The placenta serves as an important biological barrier with the ability to allocate nutrients, hormones, and growth factors to the fetus while also limiting fetal exposure to some toxic substances. PFAS have been detected in serum from maternal, cord, and newborn blood demonstrating that these chemicals are capable of passing through the placental barrier, with estimates of the efficiency of placental transfer ranging from 30—79% ( Gützkow et al, 2012 ; Ma et al, 2021 ). In addition, breast milk has been shown to account for 83—99% of PFAS total daily intake for infants ( Haug et al, 2009 ; Sundström et al, 2011 ; Gützkow et al, 2012 ; Winkens et al, 2017 ; Liu et al, 2020 ; Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The placenta serves as an important biological barrier with the ability to allocate nutrients, hormones, and growth factors to the fetus while also limiting fetal exposure to some toxic substances. PFAS have been detected in serum from maternal, cord, and newborn blood demonstrating that these chemicals are capable of passing through the placental barrier, with estimates of the efficiency of placental transfer ranging from 30—79% ( Gützkow et al, 2012 ; Ma et al, 2021 ). In addition, breast milk has been shown to account for 83—99% of PFAS total daily intake for infants ( Haug et al, 2009 ; Sundström et al, 2011 ; Gützkow et al, 2012 ; Winkens et al, 2017 ; Liu et al, 2020 ; Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…PFAS have been detected in serum from maternal, cord, and newborn blood demonstrating that these chemicals are capable of passing through the placental barrier, with estimates of the efficiency of placental transfer ranging from 30—79% ( Gützkow et al, 2012 ; Ma et al, 2021 ). In addition, breast milk has been shown to account for 83—99% of PFAS total daily intake for infants ( Haug et al, 2009 ; Sundström et al, 2011 ; Gützkow et al, 2012 ; Winkens et al, 2017 ; Liu et al, 2020 ; Ma et al, 2021 ). Beyond direct maternal transfer, infants and toddlers may experience higher exposures than adults for several additional reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Fetuses are highly sensitive to xenobiotics, so early life exposure could have strong and persistent impacts on normal development. Numerous studies have verified that PFASs can penetrate the placental barrier and reach the embryos through umbilical cord blood, relating to adverse health effects and birth outcomes of fetuses, such as low birth weight, decrease in immune function, and endocrine disorder. However, mass balance analysis results showed that an average of 9% of extractable organofluorine (EOF) was unidentified in cord serum, indicating the presence of unknown PFASs in exposed fetuses . Consequently, the novel PFASs identification in cord blood and their relationship with birth outcomes are essential to evaluate prenatal exposure risk of PFASs.…”
Section: Introductionmentioning
confidence: 99%
“…A developing fetus is especially vulnerable to toxicants, raising significant concerns over children's health. [1][2][3] The most common developmental abnormalities are attributed to maternal exposure to toxins. 4 Recognizing the increasing applications of nanoparticles (NPs) in commercial products, evidence accumulates that certain NPs can overcome the placental barrier and pose adverse effects on fetal development.…”
Section: Introductionmentioning
confidence: 99%